Montague Glass quotation - Glass, Montague, 1877-1934.
Signed quotation (1913 January 12; Nice, Alpes-Maritimes).
Humorist and playwright.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: American wit and humor; Humorists; Playwrights